(2x)/(2x-3) - (3x)/(2x+3) = (15-32x^2)/(4x^2-9) Решите,пожалуйста :С

(2x)/(2x-3) - (3x)/(2x+3) = (15-32x^2)/(4x^2-9) Решите,пожалуйста :С
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{2x}{2x - 3} - \frac{3x}{2x+3} = \frac{15-32x^2}{4x^2 - 9} [/latex] [latex]2x(2x + 3) - 3x(2x - 3) = 15 - 32x^2[/latex] [latex]15x - 2x^2 = 15 - 32x^2 [/latex] [latex]30x^2 + 15x - 15 = 0[/latex] [latex]15(x + 1)(2x - 1) = 0[/latex] [latex]|(:15)[/latex] [latex](x + 1)(2x - 1) = 0[/latex] [latex]x + 1 = 0 ; 2x - 1 = 0[/latex] [latex]x = -1 ; 2x = 1[/latex] [latex]x1 = -1 x2 = 0.5[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы